Penyuluhan Dan Pendampingan Digitalisasi Keuangan Serta Penentuan Hpp Pada Usaha “Bila Catering” Di Desa Tegalrejo - Wulandari Hidayanti; Nanda Wahyu Indah Kirana (Cv. Utility Project Solution, 2023)
In the current era of technological development, MSME players are expected to have the ability to master and take advantage of Digitalization. The development of digitalization provides opportunities for progress in all fields. The field of accounting itself is one of them regarding digital bookkeeping. Bookkeeping is very important in accounting. Currently, there are still many MSMEs that do not know and understand related to recording and preparing financial reports. In addition, many MSMEs, when evaluated regarding the cost of production in determining the selling price, often set the selling price based on the price on the market, so they do not know for sure the profit they get. Therefore, there is a need for socialization and assistance for MSME actors in conducting financial processing using the Application Buku Warung and calculating the Cost of Goods Manufactured. The goal is that MSME actors can find out simple recording or bookkeeping through applications that can be carried everywhere, as well as the actual selling price. The advantages can also increase the awareness of MSME actors in financial reporting. The implementation of this community service is in Tegalrejo Probolinggo Village, namely at the UMKM